Wittgenstein’s View of Aesthetics - Žiemytė, Rasa (Problemos, 1998)
Considering that dominant interpretation of Wittgenstein’s philosophy ignores what stands outside of linguistic expressions and what Wittgenstein himself names as extremely important, the special attention to ’about what it is necessary to be silent’ is paid in the article. Early and the later Wittgenstein’s views to aesthetic in the context of his language conceptions are analysed here. In “Tractatus” aesthetics is one form of mysterious experience of the world as the limited whole. It reveals experiencing subject, which is the limit of the world and language. The description of “aesthetic” language games in later philosophy of Wittgenstein shows that aesthetic experiences do not enter into the language. Aesthetic vocabulary is used only as marks when these experiences happen. The unexplainability of aesthetic experiences means, that they are not causal in its origin.